2000
DOI: 10.1074/jbc.m007586200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Functional Characterization of Inositol 1,3,4,5,6-Pentakisphosphate 2-Kinases

Abstract: Synthesis of inositol 1,2,3,4,5,6-hexakisphosphate (IP 6 ), also known as phytate, is integral to cellular function in all eukaryotes. Production of IP 6 predominately occurs through phosphorylation of inositol 1,3,4,5,6-pentakisphosphate (IP 5 ) by a 2-kinase. Recent cloning of the gene encoding this kinase from Saccharomyces cerevisiae, designated scIpk1, has identified a cellular role for IP 6 production in the regulation of mRNA export from the nucleus. In this report, we characterize the biochemical and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 50 publications
(107 reference statements)
3
74
0
Order By: Relevance
“…Several observations suggest that Gle1 activates Dbp5 in a manner that requires the small metabolite inositol hexakisphosphate (InsP 6 ) 114,115 . Mutations in the InsP 6 pathway genetically interact with gle1 mutants 122 and, in vitro, InsP 6 further increases the Gle1-dependent stimulation of Figure 4 | Regulation of eIF4A during translation initiation. a | During cap-dependent initiation of translation, eukaryotic initiation factor 4A (eIF4A) binds ATP, eIF4G and RNA (top).…”
Section: Nuclear Specklesmentioning
confidence: 99%
“…Several observations suggest that Gle1 activates Dbp5 in a manner that requires the small metabolite inositol hexakisphosphate (InsP 6 ) 114,115 . Mutations in the InsP 6 pathway genetically interact with gle1 mutants 122 and, in vitro, InsP 6 further increases the Gle1-dependent stimulation of Figure 4 | Regulation of eIF4A during translation initiation. a | During cap-dependent initiation of translation, eukaryotic initiation factor 4A (eIF4A) binds ATP, eIF4G and RNA (top).…”
Section: Nuclear Specklesmentioning
confidence: 99%
“…We identified the Arabidopsis orthologs of Ipk2 and Ipk1 through BLAST sequence homology searches. The IP 5 2-kinase amino acid sequences from Saccharomyces cerevisiae, Schizosaccharomyces pombe, and Candida albicans (13) were used as queries against the Arabidopsis genome database. Three candidate genes were identified, two of which appeared to be pseudogenes.…”
Section: Atipk1mentioning
confidence: 99%
“…Pathways (I) and (II) are inositol lipid-dependent, whereas pathway (III) does not require lipid synthesis. Pathway (I) initiates through phospholipase C and subsequent sequential phosphorylation of inositol 1,4,5-trisphosphate [I(1,4,5)P 3 ] by IP kinases (IPKs), IPK2 (7)(8)(9)(10)(11)(12) and IPK1 (13)(14)(15). Pathway (II) is also a phospholipasedependent pathway whereby I(1,4,5)P 3 is phosphorylated to inositol 1,3,4,5-tetrakisphosphate [I(1,3,4,5)P 4 ] by either Ipk2 or I(1,4,5)P 3 3-kinase, dephosphorylated to inositol 1,3,4-trisphosphate [I(1,3,4)P 3 ], and phosphorylated by a I(1,3,4)P 3 5͞6-kinase, Ipk2, and Ipk1, respectively, through the indicated intermediates (14,(16)(17)(18).…”
mentioning
confidence: 99%
“…Purification of a protein corresponding to this kinase activity from immature soybean seeds revealed that the enzyme had a molecular mass of 52,000 D as determined by SDS-PAGE and a pH optimum at 6.8 (Phillippy et al, 1994). More recently, progress on characterization of this kinase at the molecular level has followed the discovery of the Ins(1,3,4,5,6)P 5 2-kinase gene (IPK1) in budding yeast (York et al, 1999;Ives et al, 2000). Orthologs of IPK1 were subsequently isolated from Schizosaccharomyces pombe (Ives et al, 2000), human (Verbsky et al, 2002), Drosophila (Seeds et al, 2004), and Arabidopsis (Stevenson-Paulik et al, 2005;Sweetman et al, 2006).…”
mentioning
confidence: 99%
“…More recently, progress on characterization of this kinase at the molecular level has followed the discovery of the Ins(1,3,4,5,6)P 5 2-kinase gene (IPK1) in budding yeast (York et al, 1999;Ives et al, 2000). Orthologs of IPK1 were subsequently isolated from Schizosaccharomyces pombe (Ives et al, 2000), human (Verbsky et al, 2002), Drosophila (Seeds et al, 2004), and Arabidopsis (Stevenson-Paulik et al, 2005;Sweetman et al, 2006). T-DNA insertional disruption of the Arabidopsis AtIPK1 gene was shown to result in accumulation of Ins (1,3,4,5,6)P 5 in seeds, and Arabidopsis lines containing insertional disruptions in both AtIPK1 and AtIPK2b gave rise to phytate-free seeds (Stevenson-Paulik et al, 2005).…”
mentioning
confidence: 99%